Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To simplify the given expression:
[tex]\[ 4^{-\frac{11}{3}} \div 4^{-\frac{2}{3}} \][/tex]
we will use properties of exponents. Specifically, we use the rule that states:
[tex]\[ \frac{a^m}{a^n} = a^{m-n} \][/tex]
Here, [tex]\(a = 4\)[/tex], [tex]\(m = -\frac{11}{3}\)[/tex], and [tex]\(n = -\frac{2}{3}\)[/tex]. Substituting these values into the rule, we get:
[tex]\[ 4^{-\frac{11}{3}} \div 4^{-\frac{2}{3}} = 4^{-\frac{11}{3} - (-\frac{2}{3})} \][/tex]
Next, we need to perform the subtraction inside the exponent:
[tex]\[ -\frac{11}{3} - (-\frac{2}{3}) = -\frac{11}{3} + \frac{2}{3} \][/tex]
To subtract these fractions, we combine them into a single fraction:
[tex]\[ -\frac{11}{3} + \frac{2}{3} = -\frac{11 - 2}{3} = -\frac{9}{3} \][/tex]
Now, simplify the fraction:
[tex]\[ -\frac{9}{3} = -3 \][/tex]
So, the expression simplifies to:
[tex]\[ 4^{-3} \][/tex]
To further simplify, we use the property of negative exponents, which states:
[tex]\[ a^{-n} = \frac{1}{a^n} \][/tex]
Applying this property to our expression:
[tex]\[ 4^{-3} = \frac{1}{4^3} \][/tex]
Now calculate [tex]\(4^3\)[/tex]:
[tex]\[ 4^3 = 4 \times 4 \times 4 = 64 \][/tex]
Therefore:
[tex]\[ 4^{-3} = \frac{1}{64} \][/tex]
Hence, the simplified form of the expression is:
[tex]\[ \frac{1}{64} \][/tex]
The correct answer is:
A. [tex]\(\frac{1}{64}\)[/tex]
[tex]\[ 4^{-\frac{11}{3}} \div 4^{-\frac{2}{3}} \][/tex]
we will use properties of exponents. Specifically, we use the rule that states:
[tex]\[ \frac{a^m}{a^n} = a^{m-n} \][/tex]
Here, [tex]\(a = 4\)[/tex], [tex]\(m = -\frac{11}{3}\)[/tex], and [tex]\(n = -\frac{2}{3}\)[/tex]. Substituting these values into the rule, we get:
[tex]\[ 4^{-\frac{11}{3}} \div 4^{-\frac{2}{3}} = 4^{-\frac{11}{3} - (-\frac{2}{3})} \][/tex]
Next, we need to perform the subtraction inside the exponent:
[tex]\[ -\frac{11}{3} - (-\frac{2}{3}) = -\frac{11}{3} + \frac{2}{3} \][/tex]
To subtract these fractions, we combine them into a single fraction:
[tex]\[ -\frac{11}{3} + \frac{2}{3} = -\frac{11 - 2}{3} = -\frac{9}{3} \][/tex]
Now, simplify the fraction:
[tex]\[ -\frac{9}{3} = -3 \][/tex]
So, the expression simplifies to:
[tex]\[ 4^{-3} \][/tex]
To further simplify, we use the property of negative exponents, which states:
[tex]\[ a^{-n} = \frac{1}{a^n} \][/tex]
Applying this property to our expression:
[tex]\[ 4^{-3} = \frac{1}{4^3} \][/tex]
Now calculate [tex]\(4^3\)[/tex]:
[tex]\[ 4^3 = 4 \times 4 \times 4 = 64 \][/tex]
Therefore:
[tex]\[ 4^{-3} = \frac{1}{64} \][/tex]
Hence, the simplified form of the expression is:
[tex]\[ \frac{1}{64} \][/tex]
The correct answer is:
A. [tex]\(\frac{1}{64}\)[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.